2010
DOI: 10.1007/s10532-010-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of cattle manure under mesophilic and thermophilic conditions: characterization of organic matter applying thermal analysis and 1H NMR

Abstract: Digestion of cattle manure collected from a livestock farm together with bedding material (straw) has been studied under mesophilic and thermophilic conditions in batch reactors. The digestion was carried out for a prolonged period with the aim of evaluating the changes undergone by the organic matter. The mesophilic digestion carried out revealed a greater capacity to produce gas and transform organic matter, while a higher conversion rate, but a lower gas yield, was obtained under thermophilic conditions. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 56 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…Therefore, both methane potential and rate decreased for the sets of MW pretreatment. Studying kinetics of biogas production from cattle manure, Budiyono et al [31] [33]. The results of the untreated manure sets in this study were comparable to their findings.…”
Section: Setsupporting
confidence: 83%
“…Therefore, both methane potential and rate decreased for the sets of MW pretreatment. Studying kinetics of biogas production from cattle manure, Budiyono et al [31] [33]. The results of the untreated manure sets in this study were comparable to their findings.…”
Section: Setsupporting
confidence: 83%
“…A c c e p t e d M a n u s c r i p t 11 illustrated that the cow manure had the highest content of cellulose and lignin components among the three manures, which was in according to the previous articles [11,42].…”
Section: Page 11 Of 26mentioning
confidence: 58%
“…In this regard the use of thermophilic conditions in LBRs treating spent cow bedding could represent an effective solution to enhance the process performance. Indeed, when comparing the influence of mesophilic and thermophilic temperatures, several authors agreed on the faster degradation kinetics when using thermophilic conditions to treat different substrates such as: spent horse bedding (Böske et al, 2015), the organic fraction of municipal solid waste (Fernández-Rodríguez et al, 2013), spent cow bedding (Gómez et al, 2011), wood chips (Hegde and Pullammanappallil, 2007) and cow dung (Jha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, few data comparing mesophilic and thermophilic treatment are available on spent animal bedding consisting of faeces and straw. Böske et al (2015) used a continuous upflow anaerobic solid-state (UASS) reactor to treat spent horse bedding, whereas Gómez et al (2011) used a dry unmixed batch system to digest spent cow bedding. In thermophilic conditions, the first authors observed higher kinetics and methane yield than at mesophilic temperature, while the second reported higher kinetics and a lower methane yield.…”
Section: Introductionmentioning
confidence: 99%